Cet ouvrage fait partie de la bibliothèque YouScribe
Obtenez un accès à la bibliothèque pour le lire en ligne
En savoir plus

# University of Illinois at Urbana Champaign Fall

4 pages
University of Illinois at Urbana-Champaign Fall 2006 Math 380 Group G1 Midterm III. Monday, December 4. 50 minutes You are not allowed to use your lecture notes, textbook, or any other kind of documentation. Calculators, mobile phones and other electronic devices are also prohibited. 1.(10 points) Let ? be the curve of equation x(t) = t, y(t) = esin(2pit), z(t) = ln(1 + t2), for 0 ≤ t ≤ 1, oriented in the direction of increasing t. Compute ∫ ? (3x2 + 3yz + ez)dx + (3xz + 3y2)dy + (3xy + xez)dz. Correction. Looking at the curve, and the line integral, one can guess that there is a trick here ; indeed, if one lets f(x, y, z) = x3 + y3 + 3xyz + xez then the integral is equal to ∫ ? ∂f ∂x dx + ∂f ∂y dy + ∂f ∂z dz. Hence the integral is equal to f(B)? f(A), where A,B are the endpoints of the curve (B is the point corresponding to t = 1, A correspond to t = 0).

• pointing away

• divergence theorem seems

• urbana-champaign fall

• y6 ?

• normal vector

• ∂f ∂x

Voir plus Voir moins
##### Surface normal

Vous aimerez aussi

1.
sin(2πt) 2γ x(t) = t y(t) = e z(t) = ln(1 + t ) 0 ≤ t ≤ 1Z
2 z 2 zt (3x +3yz +e )dx+(3xz +3y )dy +(3xy +xe )dz
γ
Z
∂f ∂f ∂f3 3 zf(x,y,z) = x +y + 3xyz +xe dx+ dy + dz
∂x ∂y ∂zγ
f(B)−f(A) A,B B
t = 1 A t = 0
Z
2 z 2 z(3x +3yz +e )dx+(3xz +3y )dy +(3xy +xe )dz = (1+1+3ln(2)+2)−(0+1+0+0) = 3+3ln(2) .
γ
orinthetegral,Io,neecanofgoinuess).thatlethererisallaendptricotherktohereto;ofindeed,tifdoneuteslets,liGroupthetandaree,tscurvethetheatcorrespokingnesLocorrespCorrection.cumentation..yieldsComputeother.oincreasingeofusedirectionaltheouin50tedborienMondathenMidtermtheMathinaigntseelegraltheisoinequaloftocurv,(foris,p,t,ondingequationandofphoemobilecurvondtheCalculators,eobThisLetdets)kindoinanypok,(10extbd.notes,ectur.yourHencetotlowehnotearinYtegralminis4.equaletoDecemohibityrI.pIalsoG1e380ar2006esFdevicUrbana-Champonica,IllinoiwhereUniversityctrn2.
2 2S x≥ 0 y ≥ 0 x +y = 1 0≤ z ≤ 2ZZ
3 z 2 2~ ~F(x,y,z) = (x +sin(yz)+e ,x+z ,3zy −x) F ·~ndσ
S
∂F ∂F ∂Fx y z 2 2~(F) = + + = 3x +0+3y .
∂x ∂y ∂z
2 2 2x +y = r
ZZ Z Z Z Z Z2 1 π/2 2 1
π π 3 3π2 3~F ·~ndσ = 3r ·rdrdθdz = 3r drdz = ·2· = .
2 2 4 4S z=0 r=0 θ=0 z=0 r=0
2 2 2S 1 (x,y,z) x +y +z = 1 z≥ 0ZZ
(2xy +z)dσ
S
x = sin(ϕ)cos(θ) y = sin(ϕ)sin(θ)
πz = cos(ϕ) 0≤ θ ≤ 2π 0≤ ϕ≤ dσ2
     
2−sin(θ)sin(ϕ) cos(θ)cos(ϕ) cos(θ)sin (ϕ)
∂P ∂P 2     × = cos(θ)sin(ϕ) × sin(θ)cos(ϕ) = sin(θ)sin (ϕ)
∂θ ∂ϕ
0 −sin(ϕ) cos(ϕ)sin(ϕ)
sin(ϕ)
Z Z Z Zπ/2 2π π/2 2π sin(2ϕ)3 3I = 2sin (ϕ)cos(θ)sin(θ)+sin(ϕ)cos(ϕ) dθdϕ = sin(2θ)sin (ϕ)+ dθdϕ
2ϕ=0 θ=0 ϕ=0 θ=0
Z π/2 sin(2ϕ)
I = 2π dϕ = π .
2ϕ=0
3S x+y +z = 1 x≥ 0 y≥ 0 z≥ 0 ZZ
2~ ~ ~F F(x,y,z) = (x+y +z,y−1,z) F ·~ndσ
S
3z = 1−x−y
3x,y 0≤ x 0≤ y x+y ≤ 1
2 2 2 3 2 2 3~F·~ndσ =±(x+y +z,y−1,z)·(1,3y ,1)dxdy = (x+y +z+3y −3y +z)dxdy = (−x−2y +y +2)dxdy
3f(x,y,z) = x+y +z
S z x,y f
f S f
f
3Z Z Z1 1−y 1 3 2 (1−y )2 3 2 3 3 3 3
I = −x−2y +y +2 dxdy = − −2y (1−y )+y (1−y )+2(1−y ) dy
2y=0 x=0 y=0
Z 1 3 3 3 3 2 1 206 2 5
I = − y −2y +2y dy = − − + = .
2 2 2 14 3 3 21y=0